PHYTOCHEMICAL SCREENING AND IN VITRO ANTIOXIDANT POTENTIALS OF EXTRACTS OF TEN MEDICINAL PLANTS USED FOR THE TREATMENT OF DIABETES MELLITUS IN SRI LANKA - Attanayake, Anoja Priyadarshani; Jayatilaka, Kamani Ayoma Perera Wijewardana; Pathirana, Chitra; Mudduwa, Lakmini Kumari Boralugoda (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Over the last decade, extensive research work has focused on the potential health benefits of antioxidants while many medicinal plant extracts have been evaluated for their antioxidant profile. Medicinal plants selected for this study are widely used in traditional medicine for the treatment of diabetes mellitus in Sri Lanka some of which are recommended as dietary supplements to the existing therapies. The present study aimed at determining the total polyphenol contents and total antioxidant activities of aqueous extracts of 10 selected Sri Lankan medicinal plants by three in vitro methods; Materials and Methods: DPPH(2, 2-diphenyl-2-picrylhydrazyl), FRAP (ferric reducing power) and NO (nitric oxide) assays. The aqueous plant extracts were tested at the concentration of 0.05 g/mL. The total polyphenol content was determined according to the Folin-Ciocalteu method while the total antioxidant activity was evaluated by DPPH, FRAP and NO assays with L-ascorbic acid as reference compound. Results: The total polyphenol content of the plant extracts varied from 0.41 to 13.00 mg GAE (gallic acid equivalents) per gram dry weight. The antioxidant activities ranged in IC50 of 36.89-101.27 µg/mL, IC50 of 139.56-419.93 µg/mL, 0.12-8.98 µM for DPPH, NO, FRAP assays, respectively. A significant positive correlation was observed between total polyphenol content and antioxidant activities (P< 0.05). Conclusion: Phytochemical analysis revealed the presence of polyphenolic compounds, alkaloids and flavonoids in the plant materials which also possessed in vitro antioxidant potentials. Polyphenolic compounds contribute significantly to the total antioxidant capacities of medicinal plant extracts.